heart desease - Eugene Braunwald, MD, MD(Hon) ScD(Hon) FRCP (2007)
We intend Heart Disease to constitute the â€œcore curriculum,â€ an up-to-date, comprehensive, and authoritative ready reference for all practitioners. We strove to make this Eighth Edition an information source of practical clinical utility, grounded in the rapidly expanding evidence base that informs our practice. As in the previous editions of Heart Disease, we present the scientific underpinnings that govern cardiovascular pathophysiology and provide a rational basis for understanding therapeutics and management of cardiovascular diseases encountered in clinical practice.